"Sanctuario Sanctificado" defining urban cultural landscape character of selected Manila church grounds - Nadal, Cathe Desiree S. (College of Architecture, University of the Philippines Diliman, 2012)
Manila church grounds define the sacred spaces in the urban context. Although assumed as a space for religious beliefs and manifestations of the Catholic religion, these urban spaces also provide the canvas of urban spatial heritage constructs in the form of space, structure, and change. "Sanctuario Sanctificado : defining the urban cultural landscape character of selected Manila church grounds" provides a framework of the urban cultural landscape character of Manila thru the selected historic church grounds of Malate, Santa Ana, and Tondo. The study focuses on the preexisting historical, social, and physical profiles of the selected church grounds. The amalgamation shows an interrelation of urban cultural landscape characteristics thru the cross examination on the strata of space, structure, and change. Furthermore, the study defines the church grounds to be a space not just for religious manifestations and practices, but for cultural, secular, and social ones as well. The physical structure defined thru observation of user movement and usage of church grounds spaces further explains the urban linkages involved in the selected church grounds. The study of the existing physical components, landscape features, and user perception of church ground elements and spaces translates to both a quantitative and qualitative analysis of church grounds' reciprocal phenomena of change. The framework resulting from the analysis of tangible and intangible constructs yields a guideline that shall serve as a basis for several proposed design plans for the selected church grounds. It is the hope of this author that this framework will uplift the urban cultural landscape character of the church grounds as an essential open space in the context of Manila.